Analisa Keterkaitan Faktor Demografis dan Faktor Psikografis Dengan Buying Decision Warga Surabaya Akan Paket Wisata Luar Negeri yang Ditawarkan Oleh Biro Perjalanan Wisata - Selvy Cahyono (Tourism Retailing+, 2013)
Tourism is essentially a way of meeting human needs in providing spiritual and physical entertainment after some time working and have the funds to travel to visit other areas ( domestic tourism ) or other countries ( tourism abroad) . Demographics is one of the external factors that shape tourism demand . Demographic trends also helps forecasting a product for years to come as well as changes in demand and consumption patterns . Therefore the role of demographics in marketing world is very large . There are four factors that influence consumer behavior including , cultural factors , social factors , personal factors , and psychological factors . In the increasingly fierce competition , the understanding of personality , self-concept , lifestyle , and psychographic factors of consumers is one way to win the hearts of consumers as indirectly by knowing psychographic factors of consumer marketers approach was in accordance with the characteristics of the consumers themselves .